Taxocenoses de serpentes em grupos fitofisionômicos de cerrado no Parque Nacional de Sete Cidades, Piracuruca, Piauí, Brasil - ROCHA, Wáldima Alves da (Universidade Federal do Pará, 2013)
The snake fauna of the “Parque Nacional de Sete Cidades, Piraracuruca, Piauí,Brazil”, have been surveyed. Data on composition, species richness and species abundance in different habitats, patterns of daily activity, diet and reproduction are presented as well as a comparison with other areas based on species composition. Six expeditions have been made, between September 2005 and August 2006, with total of 120 days of fieldwork. Three sampling methods were used: time-constrained search (PLT), pitfall traps with drift fences (AIQ) and occasional encounters (EO). We recorded 87 snakes, belong to in four families (Boidae, Colubridae, Elapidae, Viperidae), 18 generas and 24 species. The dominant species was Thamnodynastes sp. (13,1%), followed by Oxyrhopus trigeminus and Micrurus ibiboboca (10, 3%). There was a prevalence of terrestrial species with diurnal activity. Like other assemblages of open formations, Colubridae snakes dominanted. The Cerrado Típico the largerst diversity of species, whereas the smallest diversities were registered in the Campo Limpo and Cerrado Rupestre. PLT was the most efficient method for snake sampling. However no single method alone, worked well enough and the three methods should be used together for a better sampling of the area. Through an PCO analysis and grouping analysis it was possible to observe that although the study site is floristically and fisiomically similar to the snake fauna was more similar to assemblages of areas in despite of occurring a similarity with Cerrado, the composition of species showed larger similarity faunistic with assemblages of areas Cerrado/Caatinga and Caatinga.